Evaluation of Tiletamine-Zolazepam Anaesthesia with Glycopyrrolate and Butorphanol as Preanaesthetics in Dogs - Baggavalli Puttaraju, Sapthami; Nagaraju, Narayanappa; Ramappa Balappanavar, Basavaraj; Gowda Keregallikoppalu, Hemanth; Bekkare Chandrashekaraiah, Girish; Shekyanaik, Ganganaik (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study was conducted to evaluate the efficacy and feasibility of Tiletamine-Zolazepam anaesthesia (8 mg/kg b.wt., IV) with and without Glycopyrrolate, Butorphanol as preanesthetics in dogs undergoing ovario-hysterectomy. The study was conducted in 12 clinical cases of dogs in two groups, viz., A and B with six dogs each. Group A animals were premedicated with Glycopyrrolate (10 µg/kg b.wt., IM) and Butorphanol (0.2 mg/kg b.wt., IM). In Group B no preanesthetics were administered. Onset of sedation was longer in Butorphanol (Group A) premedicated dogs, whereas the induction time, duration of anaesthesia, and recovery time were similar in both groups. Degree of analgesia was slightly longer in Group A. Degree of muscle relaxation and palpebral reflexes scores were almost similar in both the groups. Rectal temperature reduced slightly in both the groups till the end of anaesthetic period. Heart rate, respiratory rate increased significantly in both the groups, however, the values returned to baseline at the end of procedure. Electrocardiogram recorded sinus rhythm and tachycardia under the influence of Glycopyrrolate and Tiletamine. Hypertension was observed till 30th min and returned to baseline at the end of procedure. Haemato-biochemical parameters variations were non-significant in both the groups. Thus, it can be concluded that Tiletamine-Zolazepam can be safely administered to healthy patients undergoing elective surgical procedures, however, addition of Glycopyrrolate and Butorphanol could be helpful in preventing hypersalivation and provide certain extent of analgesia.